Stakeholder perspectives on the use of VoiceThread as a multimodal alternative to conventional discussion board in distance education - Chen, Julian; Bogachenko, Tetiana (Springer Nature, 2023)
This pilot study explores and documents online students’ and their lecturer’s debut experiences of utilising VoiceThread (VT), a digital multimodal platform, as an alternative discussion space via Open Universities Australia (OUA). Feedback from the lecturer’s teaching log and interview was corroborated with his OUA students’ survey responses, and analysed in relation to student online learning experiences with VT and Discussion Board, as well as technological and affective aspects of both platforms. Findings indicate that VT has a stronger potential in boosting stakeholders’ online engagement and enjoyment of distance learning, thus fostering online community building. Specifically, VT creates not only a multimodal and dynamic platform in lieu of Discussion Board, but a supportive online learning environment that promotes more inclusive and ongoing interactions. Despite the positive results, VT was viewed by some students as technologically demanding, causing them to only read peer posts without responding. It is suggested that orientation training sessions and trial threads be made available to ease the students into VT. Aspects of tutorial group size and instructor support should also be considered for future online course delivery.